Feedback in social semantic applications. (13th June 2011) - Mazarakis, Athanasios; Braun, Simone; Zacharias, Valentin
This article examines the role of feedback mechanisms in social semantic web applications. It introduces different social semantic applications and the function that system feedback can play in these, although only a small portion of possible roles of feedback in such applications is addressed by the state of the art. The authors present an approach with four concrete feedback mechanisms and an experiment on the use of explicit feedback to foster user contribution and motivation. Finally, the article details the large number of open research questions in this area.